Leadership Education with Structured Assignments For Student Class Five KMI In Darussalam Gontor Islamic Boarding School - Abu Darda; Moh Al Ahyar (Prodi Pendidikan Agama Islam, Fakultas Tarbiyah, Universitas Darussalam Gontor, 2020)
Islamic boarding schools are educational institutions that originate from, are managed by, and take part in the community. In the context of Darussalam Gontor Modern Islamic Boarding School further means that the educational process involves students as subjects not objects of education. For that reason, leadership education is a very important thing in educational institutions, namely as a basic means for an institution to improve and optimize human resources to achieve an expected goal. With one of the slogans in Darussalam Gontor Modern Islamic Boarding School that is always delivered that is ready to be led and ready to lead. So the students in Darussalam Gontor Modern Islamic Boarding School educated with a pattern so that they are ready to be led by senior students and their teachers must be ready to continue the wheels of management in the boarding house by leading their junior students. In scientific research, researchers used a qualitative field approach followed by the type of research, research location, data sources and data collection methods. This research is a qualitative research because the research was conducted in natural conditions. The main problem in providing leadership education for students is the large number of them and they are not known about their specific and general duties, as well as some students who are difficult to advise and warn because of their work, enthusiasm and awareness. And students who transcend order and discipline as they continue the action with repetition.